PEMETAAN INDEKS PRODUKTIVITAS TANAH PADA LAHAN PERKEBUNAN DI ATP JATIKERTO, KECAMATAN KROMENGAN, KABUPATEN MALANG - Destantri Krisdiati; S Soemarno; Mochtar Lutfi Rayes (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
It is feared that the decline in productivity of plantation crops in Malang Regency, so it is necessary to analyze the soil productivity index at ATP Jatikerto as one of the locations for producing plantation plants. This soil productivity index assessment was presented in the form of a map to make it easier to see the distribution pattern of soil productivity in ATP Jatikerto. The results of the calculation of the productivity index showed that the land potential varied from land with poor to sufficient criteria, namely maize land with an IP (Productivity Index) of 43.27, which is included in the bad IP criteria. In coffee, cocoa, sugarcane, papaya, and citrus fields, they are categorized as moderate with IPs of 50.14, respectively; 45.82; 39.45; 52.26; and 45.82. Actions that can be taken to overcome the problem of decreasing productivity are to carry out regular fertilization, both organic and inorganic, to keep nutrients available for cultivated plants, as well as adding organic matter using litter which not only serves to add nutrients but can also be used as organic mulch to prevent raindrops from falling directly to the ground so that the loss of topsoil can be minimized and increase the population of soil microorganisms. In addition, it can also use bagasse, blotong or manure which can improve the physical condition of the soil by reducing soil density and increasing macropores for better root growth, and ultimately increasing sugarcane yield.